Contradictory Mechanisms of rheumatoid arthritis and hepatitis B virus infection activation - Fenglin Zhu; Miao Wang; Xuhong Zhang; Guoqing Zhao; Hongyan Gao; Lamei Zhou (Heliyon)
Rheumatoid arthritis (RA) is associated with a high rate of hepatitis B virus (HBV) infection. A large proportion of HBV reactivation may occur in RA patients after immunosuppression treatment, while fulminant hepatitis may occur in severe cases. Immunosuppressants are fundamental medications for the treatment of RA but carry the risk of inducing HBV reactivation. This inherent contradiction poses challenges throughout the immunosuppressive treatment process in patients with RA. Recently, numerous studies have been conducted on the contradictory therapeutic mechanisms between RA treatment and HBV infection, including aspects of innate immunity, adaptive immunity, and related signalling pathways. In this article, we review the immunological mechanisms underlying the onset of RA and HBV infections, providing a reference for determining appropriate treatment plans to reduce therapeutic contradictions and thereby reduce the risk of HBV reactivation in patients with RA combined with HBV infection.